Short Communication: Digital identification approach to characterize Hevea brasiliensis leaves - BAYU PRATOMO; LISNAWITA LISNAWITA; TENGKU CHAIRUN NISA; Mohammad Basyuni (Society for Indonesian Biodiversity, 2021)
Abstract. Pratomo B, Lisnawita, Nisa TC, Basyuni M. 2021. Short Communication: Digital identification approach to characterize Hevea brasiliensis leaves. Biodiversitas 22: 1006-1013. The purity of clones is a key factor to obtain uniform growth of Hevea brasiliensis Muell Arg in the field. Crop uniformity has an impact on production patterns that can be predicted in latex content. Basically, H. brasiliensis tree leaves show similarities to each other such as the color, texture, or shape of the leaves. Identification of clones that have been very common by the morphology of H. brasiliensis leaves. This study links the results of previous research on digital methods used. A total of 27 clones were sampled in this study which came from the garden collection of entres, which can be used as a source of elders for assisted pollination or source of planting materials for the needs of production-scale seeds in the field. Here, we used a database of 540 leaves from 27 clones and 10 quantitative characters to address these issues The analysis data used a randomized complete block design (RCBD) factorial. The result showed the identification method digitally on characterizing of leaves by using Software Adobe Photoshop, depicting that the characteristics contained in H. brasiliensis leaves are very proper to be used as the first character in identifying an H. brasiliensis clone. The present work provided a piece of important information on the characterization of H. brasiliensis leaves to enhance the selection of parent clones.